Household's awareness and participation in sustainable electronic waste management practices in Saudi Arabia - Abdulaziz I. Almulhim (Ain Shams Engineering Journal, 2022)
Electronic waste (e-waste) management is currently a priority, especially in economically developing nations, because improper waste disposal leads to economic loss and negative impacts on environment and public health. The aim of this study is to evaluate household awareness of e-waste, environmental problems associated with improper disposal, and willingness to engage in managing e-waste. Using a snowball sampling method, an online questionnaire was administered to 523 respondents to gather data on household knowledge of waste management. Data were analyzed using statistical methods such as one-way ANOVA and t-tests. Of the participants, 70.1% claimed that they had not been educated on how e-waste poses a serious environmental problem, and 88.35% were willing to take part in managing waste after developing a proper understanding. Respondents in the study processed e-waste as if it were another sort of urban solid trash. E-waste was discarded by storing it in their home (45%) or discarding it with other household waste (32%). This was due to a lack of recycling options and poor understanding about the benefits and potentials of recycling e-waste, among other issues. The study made suggestions regarding educational interaction and raising public knowledge concerning e-waste, and it presented a practical e-waste management approach and concept. In addition, the paper presents a practical e-waste management approaches and concepts; like Value-Belief Norm and Extended Producer Responsibility might be implemented and used in tomorrow's Saudi. This paper can assist legislators and government organizations in Saudi Arabia and other developing countries in promoting awareness regarding e-waste management, eventually helping Saudi Arabia meet its Vision 2030 targets regarding sustainable production and consumption.